Intracranial Hematoma Detection by Near Infrared Spectroscopy in a Helicopter Emergency Medical Service: Practical Experience. (22nd June 2017) - Schober, Patrick; Bossers, Sebastiaan M.; Schwarte, Lothar A.
Abstract : In (helicopter) emergency medical services, (H)EMS, the prehospital detection of intracranial hematomas should improve patient care and the triage to specialized neurosurgical hospitals. Recently, noninvasive detection of intracranial hematomas became possible by applying transcranial near infrared spectroscopy (NIRS). Herein, second-generation devices are currently available, for example, the Infrascanner 2000 (Infrascan), that appear suited also for prehospital (H)EMS applications. Since (H)EMS operations are time-critical, we studied the Infrascanner 2000 as a "first-time-right" monitor in healthy volunteers (n = 17, hospital employees, no neurologic history). Further, we studied the implementation of the Infrascanner 2000 in a European HEMS organization (Lifeliner 1, Amsterdam, The Netherlands). The principal results of our study were as follows: The screening for intracranial hematomas in healthy volunteers with first-time-right intention resulted in a marked rate of virtual hematomas (false positive results, i.e., 12/17), rendering more time consuming repeat measurements advisable. The results of the implementation of the Infrascanner in HEMS suggest that NIRS-based intracranial hematoma detection is feasible in the HEMS setting. However, some drawbacks exist and their possible solutions are discussed. Future studies will have to demonstrate how NIRS-based intracranial hematoma detection will improve prehospital decision making in (H)EMS and ultimately patient outcome.